KARAKTERISTIK IBU BERSALIN DENGAN SEKSIO SESAREA DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2013-2014 - evita sartika hutagalung; Hiswani .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Caesarean section is giving birth of fetus by abdominal wall dissection and uterus wall. At Santa Elisabethhospital, in 2013-2014the proportion of Caesarean section is 71%. The intention of the study were to the determine characteristics of the mother who underwent caesarean section at Santa Elisabeth Hospital Medan 2013-2014. Descriptive study using a case series design has been conducted. The Population was 352 mothers who is underwent Caesarean section lodge counted, 77 cases a sample, and sampling  was systematic random sampling. The highest proportion of mother who gave birth based on sociodemograph is in of the age group is 20-35 years old (81,8%), Bataknese (88,3%), Christian (62,3%),enterpreneur/private employee (46,8%). The most medico obstetrics factor on nullipara 46,8%,the distance of giving a birth > 2 years (80,5%),no history of disease (89,6%),no history of pregnancy (90,9%),the caesarean section history (73,2%),nocomplication(92,2%),medical indication (92,2%),the previous caesarean section history (53,7%), fetus dislocation (47,1%),Length of stay>3 days (76,6%),own expense (75,3%),return after recovered (94,8%).The results of the statistical test with exact fisher shows that there were no significant differences between maternal age with indications of cesarean section (p=0,702), maternal parity(p=0,073) with indications of cesarean section.There were no significant differences between length of stay with history of disease(p=0,397); mother pregnancy history (p=0,668); complication (p=0,570); caesarean section indications (p=0,430). Health professions are expected to provide an informationabout the negative impacts to the mother and baby if doing caesarean section and the benefits of doing a normal parturition.The pregnant mothers are expected to do gymnastics pregnant before delivery to avoid the risk factors that lead to indications for cesarean section deliveries performed. Keywords : Caesarean section, characteristics